Pondok Pesantren's Transformational Leadership Analysis of the Financial Reporting Company's Accountability - Ali Hardana (Penerbit Goodwood, 2024)
Purpose: It is not possible to evaluate the accountability of Islamic boarding schools in terms of openness as ideal, efficient, or successful. The question that arises is whether transformational leadership and trust affect the accountability of Darul Istiqomah Hutapadang Islamic Boarding School’s financial reports. This study sought to ascertain how transformational leadership and trust affect financial report accountability at Darul Istiqomah Hutapadang Islamic Boarding School. Methodology/approach: The research method used in this study was to use quantitative methods with multiple linear regression analysis using descriptive statistics, validity test, reliability test, normality test, classical assumption test, multicollinearity test, heteroscedasticity test, hypothesis test and multiple linear regression analysis test to obtain the results of the study used the SPSS version 26 application, the data used in this study were primary data obtained directly from the answers of 30 respondents who were teachers and staff of the Islamic boarding school office. Results: The findings indicate that while transformational leadership has a largely negative impact on accountability, the trust variable has a partially positive impact. Accountability is simultaneously influenced by both transformative leadership and trust. Limitations: Ownership structure and ownership has no relationship with debt policy Contribution: Ayu Lestari Indri (2022) The study's findings show that dividend policy, domestic institutional ownership, and foreign institutional ownership all significantly and favorably affect firm value. The effect of foreign institutional ownership on dividend policies is substantial and detrimental. Domestic institutional ownership has no impact on dividend policy. Foreign Institutional Ownership of Firm Value cannot be mediated by Dividend Policy as an intervening variable. Dividend Policy cannot mediate Domestic Institutional Ownership of Firm Value as an intervening variable.